2001
DOI: 10.1128/jvi.75.12.5627-5637.2001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Tick-Borne Encephalitis Virus to BHK-21 Cells Results in the Formation of Multiple Heparan Sulfate Binding Sites in the Envelope Protein and Attenuation In Vivo

Abstract: Propagation of the flavivirus tick-borne encephalitis virus in BHK-21 cells selected for mutations within the large surface glycoprotein E that increased the net positive charge of the protein. In the course of 16 independent experiments, 12 different protein E mutation patterns were identified. These were located in all three of the structural domains and distributed over almost the entire upper and lateral surface of protein E. The mutations resulted in the formation of local patches of predominantly positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 71 publications
(100 reference statements)
8
172
1
Order By: Relevance
“…4) that facilitates removal of viruses from the animal's circulation, preventing interaction with the specific cell types needed to produce vesicular disease. Taken together, our results support an expanding body of literature on the acquisition of HS binding by experimentally propagated viruses and the role of this altered receptor specificity in attenuation (10,12,13,25,30,33,34,38). In these cases, the ability to bind to HS appears to correlate with the finding that attenuated viruses are rapidly cleared from the circulation, preventing systemic spread and disease.…”
Section: Discussionsupporting
confidence: 74%
“…4) that facilitates removal of viruses from the animal's circulation, preventing interaction with the specific cell types needed to produce vesicular disease. Taken together, our results support an expanding body of literature on the acquisition of HS binding by experimentally propagated viruses and the role of this altered receptor specificity in attenuation (10,12,13,25,30,33,34,38). In these cases, the ability to bind to HS appears to correlate with the finding that attenuated viruses are rapidly cleared from the circulation, preventing systemic spread and disease.…”
Section: Discussionsupporting
confidence: 74%
“…This minimizes genetic artefacts caused by adaptation and/or replication by RNA polymerase. It is known that TBEV can change genetic and phenotypic properties relatively quickly, within 4-8 passages, during adaptation to model systems, either cell cultures, or laboratory animals (Mandl et al, 2001;Romanova et al, 2007). That's why the ''tick'' sequences of their genomes have the greatest interest for studying TBEV evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Glycoprotein E homodimers is located parallel to the lipid membrane on the outer surface of the virus particles (Rey et al, 1995). It was shown that the majority of mutations that alter the properties of a pathogenic virus are grouped within domains of the envelope glycoprotein E (Mandl et al, 2001;Ternovoi et al, 2003;Hayasaka et al, 2004;Romanova et al, 2007). The nucleotide sequence corresponding to the N-terminus of the glycoprotein E, is variable and is therefore often used for genotyping TBEV isolates, for differential genetic diagnosis of TBE and in phylogenetic studies (Hayasaka et al, 1999;Ternovoi et al, 2003;Kovalev et al, 2009Kovalev et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information is shown for 5' NTR, E, and NS4B in Table 1, and the information of the remaining silent mutations is shown in Table 2. Compared with conservative amino acid substitutions, the nonconservative mutations are of major importance, because they confer a change in charge or side-chain polarity (15,18). Amino acid substitutions were designated as conservative or nonconservative mutations as previously described (30).…”
Section: Sequence Analysismentioning
confidence: 99%